Adhesion, biofilm formation, cell surface hydrophobicity, and antifungal planktonic susceptibility: relationship among Candida spp. - Silva-Dias, Ana; Miranda, Isabel M.; Branco, Joana; Monteiro-Soares, Matilde; Pina-Vaz, Cidália; Rodrigues, Acácio G. (Frontiers in Microbiology, 2015)
We have performed the characterization of the adhesion profile, biofilm formation, cell surface hydrophobicity (CSH) and antifungal susceptibility of 184 Candida clinical isolates obtained from different human reservoirs. Adhesion was quantified using a flow cytometric assay and biofilm formation was evaluated using two methodologies: XTT and crystal violet assay. CSH was quantified with the microbial adhesion to hydrocarbons test while planktonic susceptibility was assessed accordingly the CLSI protocol for yeast M27-A3 S4. Yeast cells of non-albicans species exhibit increased ability to adhere and form biofilm. However, the correlation between adhesion and biofilm formation varied according to species and also with the methodology used for biofilm assessment. No association was found between strain's site of isolation or planktonic antifungal susceptibility and adhesion or biofilm formation. Finally CSH seemed to be a good predictor for biofilm formation but not for adhesion. Despite the marked variability registered intra and inter species, C. tropicalis and C. parapsilosis were the species exhibiting high adhesion profile. C. tropicalis, C. guilliermondii, and C. krusei revealed higher biofilm formation values in terms of biomass. C. parapsilosis was the species with lower biofilm metabolic activity.